DOING DOCTORAL RESEARCH AT A DISTANCE flourishing in off-campus, hybrid, and remote pathways. - McChesney, Katrina; Burford, James; Frick, Liezel; Koo, Tseen ([S.l.] : ROUTLEDGE, 2024)
Emerging from personal experience and empirical research, Doing Doctoral Research at a Distance is a key companion text for doctoral students from a range of research fields and geographical contexts who are undertaking off-campus, hybrid, and remote pathways. Offering guidance about the entire off-campus doctoral journey, the book introduces contexts of distance study; key information to get off to a flying start; organising time, space and plans to get work done; juggling employment, family and other commitments alongside distance study; doctoral identity and wellbeing; working with doctoral supervisors at a distance; accessing research culture at a distance; and managing the bumps along the road of the distance doctorate. Written for doctoral researchers, this book offers strategies to help those working at a distance to flourish. This book is ideally suited for those contemplating distance study, distance doctoral students who are starting their off-campus journey, and supervisors and others who are working with distance doctoral researchers. Insider Guides to Success in Academia' offers support and practical advice to doctoral students and early-career researchers. Covering the topics that really matter, but which often get overlooked, this indispensable series provides practical and realistic guidance to address many of the needs and challenges of trying to operate, and remain, in academia. These neat pocket guides fill specific and significant gaps in current literature. Each book offers insider perspectives on the often implicit rules of the game - the things you need to know but usually aren't told by institutional postgraduate support, researcher development units, or supervisors - and will address a practical topic that is key to career progression. They are essential reading for doctoral students, earlycareer researchers, supervisors, mentors, or anyone looking to launch or maintain their career in academia.
Keywords: Distance education -- Computer-assisted instruction; Doctoral students -- Social conditions; Blended learning; Education, Higher -- Web-based instruction; EDUCATION / Higher; EDUCATION / Distance Education & Learning